Trends in utilisation, perioperative outcomes, and costs of nephroureterectomies in the management of upper tract urothelial carcinoma: a 10-year population-based analysis - TİNAY, İLKER (WILEY, 2016)
Objective To perform a population-based study to evaluate contemporary utilisation trends, morbidity, and costs associated with nephroureterectomies (NUs), as contemporary data for NUs are largely derived from single academic institution series describing the experience of high-volume surgeons and it is unclear if the same favourable results occur at a national level. Patients and Methods Using the Premier Hospital Database, we captured patients undergoing a NU with diagnoses of renal pelvis or ureteric neoplasms from 2004 to 2013. We fitted regression models, adjusting for clustering by hospitals and survey weighting to evaluate 90-day postoperative complications, operating-room time (OT), prolonged length of stay (pLOS), and direct hospital costs among open (ONU), laparoscopic (LNU) and robotic (RNU) approaches. Results After applying sampling and propensity weights, we derived a final study cohort of 17 254 ONUs, 13 317 LNUs and 3774 RNUs for upper tract urothelial carcinoma (UTUC) in the USA between 2004 and 2013. During that period, minimally invasive NU (miNU) increased from 36% to 54%, while the total number of NUs decreased by nearly 20%. No differences were noted in perioperative outcomes between the three surgical approaches, including when the analysis was restricted to the highest-volume hospitals and highest-volume surgeons. The OT was longer for LNU and RNU (P < 0.001), while the pLOS rates were decreased (P < 0.001). Adjusted 90-day median direct hospital costs were higher for LNU and RNU (P < 0.001), which disappeared when adjusting for the highest-volume groups, except for RNUs performed by high-volume surgeons. Conclusions During this contemporary 10-year study, miNU has been replacing ONU for UTUC with a recent surge in RNU, along with a concurrent reduction in total NUs performed. Despite not being associated with a clinically significant improvement in perioperative outcomes, the costs for miNUs were consistently higher. However, higher hospital volumes suggest a potential cost containment strategy when performing miNUs.
Keywords: nephroureterectomy; upper urinary tract carcinoma; trend; utilisation; outcome; LAPAROSCOPIC NEPHROURETERECTOMY; ONCOLOGIC OUTCOMES; CLASSIFICATION; COMPLICATIONS; PATIENT; CANCER